Alcohol misuse, policy and treatment responses in Sub-Saharan Africa: The case of Uganda. (2nd November 2015) - Kalema, David; Vindevogel, Sofie; Baguma, Peter K.; Derluyn, Ilse; Vanderplasschen, Wouter
Abstract: Alcohol has become an important feature in the lives of many inhabitants of Sub-Saharan Africa and is increasingly associated with excessive consumption and negative personal and social consequences. Uganda is one of the Sub-Saharan countries with the highest rate of alcohol-related burden in the world, but supply and demand reduction strategies such as regulatory measures, prevention and treatment programs are hardly available. Consequently, the aim of this article is to critically review the situation in Uganda as part of a regional trend. First, the origins of alcohol misuse and emerging policy initiatives in Sub-Saharan Africa are discussed. Then, the consequences of alcohol misuse in Uganda are highlighted, as well as policy and treatment responses. Recommendations are formulated for developing more effective and culturally adapted treatment programs and policies.